Tata Kelola Kolaboratif Dalam Pengawasan Orang Asing: Analisis Peran Multiaktor di Direktorat Jenderal Imigrasi Indonesia - Daniel P. Marpaung; Seno Setyo Pujonggo; Muhammad Arief Adillah (Lembaga Pengembangan Kinerja Dosen, 2025)
Increased global mobility has made foreigner surveillance a strategic issue in Indonesia's immigration policy. This research aims to analyze how the principles of Collaborative Governance are applied in the supervision of foreigners by the Directorate General of Immigration, as well as identify the actors involved and the forms of collaboration that occur. Using a descriptive qualitative approach through documentation studies and literature review, this study found that collaborative governance has been implemented in various forms such as joint operations, data exchange, and community engagement. The collaboration involves both state (DG Immigration, Police, BIN, Ministry of Foreign Affairs) and non-state actors (media, NGOs, communities). Despite its effectiveness, collaboration still faces obstacles such as sectoral ego and the absence of a strong regulatory framework. The results of this study indicate the importance of institutional strengthening and cross-sectoral integration systems to encourage adaptive and sustainable immigration control.